Pre-service EFL Teachers’ Perception of Social Media Utilization in English - Samosir, Sri Aulia; Daulay, Sholihatul Hamidah; Dalimunte, Muhammad (JADEs Journal of Academia in English Education, 2024)
Social media advancement has affected various aspects of human life. The existence of Social media has made it easier for people, especially in the educational realm. Social media is one technology that can be used for socializing (communicating individually, in groups, etc.) between users. Despite the multifaceted functions of social media, it also serves as a learning medium with advantages and disadvantages for certain pre-service English as a Foreign Language (EFL) teachers. This research aims to identify the pros and cons of using social media in teaching English, understand the perceptions of pre-service EFL teachers regarding learning through social media, and compare social media as a learning medium to other online learning platforms. The study involved five pre-service EFL teachers from a senior high school in North Sumatra. Researchers employed a qualitative methodology, designing the research to conduct interviews with the participants, focusing on their responses to derive meaningful results. According to the pre-service EFL teachers involved in the study, using social media in teaching English is perceived as easy, comfortable, flexible, creative, and enjoyable. These positive aspects highlight social media's benefits to the teaching and learning process in the context of English instruction.